EVALUATION OF BASIC SCHOOL PROGRAM IN PASER REGENCY EAST KALIMANTAN - sri nawati (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2018)
This study aims to determine the success of the program through the correct mechanism for the preparation of supervision programs, supervision and supervisory reports conducted by elementary school supervisors in Paser Regency East Kalimantan. This is an evaluation research using Formative-Summative Model By Scriven, the subjects in this study are school supervisors, supervisor coordinators, teachers, and principals. Selection of informants in this study was conducted by purposive sampling of teachers and principals while supervisors became the main object in the study. Data analysis was done by qualitative descriptive analysis. The conclusion of the elementary school supervisory program in Paser Regency East Kalimantan is specifically through formative evaluation there has been deviation on the preparation, implementation, and reporting of the program results so that the result of summative evaluation shows the failure of the supervisor in conducting the supervision. In general, it can be concluded: 1) Elementary School Supervisor in Paser Regency has performed its duty in accordance with the regulation of the functional position of supervisor that is at least 10 schools. 2) Obstacles in the implementation of supervision of the supervisor have not been able to develop the program well. 3) Overall results of the implementation of the supervisory program cannot be used to formulate the success of education in Paser Regency East Kalimantan.